EVALUATION OF THE “POLICE GOES TO SCHOOL” CAMPAIGN IN CENTRAL JAVA BASED ON KIRK PATRICK’S RULE - Christa Vidia Rana Abimanyu; Endang Widyorini (Journal of Indonesia Road Safety, 2020)
This study aims to evaluate and provide input on the implementation of the "Police Goes to School" program in the region of Central Java. Program evaluation was carried out using Kirkpatrick's rules, namely the level of reaction, learning, and behavior. This study observed eight schools as the subjects, both secondary and high schools that had previously received the program and that never obtained it. The eight schools were purposively selected in the Resort Police of Semarang Regency and Municipality. Each school represented 40 students and 2 teachers / staff to the program. This research found that the students whose schools had received the program were satisfied with the implementation of the program, and the students had significantly higher knowledge and behavior scores to maintain traffic order signs than the students whose schools did not receive the program. Penelitian ini bertujuan untuk mengevaluasi dan memberikan masukan atas pelaksanaan program “Police Goes to School” di wilayah Jawa Tengah. Evaluasi program dilakukan dengan menggunakan kaidah Kirkpatrick yaitu tingkat reaksi, pembelajaran, dan perilaku. Studi ini mengamati delapan sekolah sebagai subyek, baik sekolah menengah pertama maupun atas yang sebelumnya telah menerima program dan tidak pernah mendapatkannya. Kedelapan sekolah tersebut dipilih secara purposif di Polrestabes Semarang. Setiap sekolah mewakili 40 siswa dan 2 guru/staf untuk program tersebut. Hasil penelitian menemukan bahwa siswa yang sekolahnya telah menerima program merasa puas dengan pelaksanaan program, dan siswa memiliki nilai pengetahuan dan perilaku yang secara signifikan lebih tinggi untuk menjaga rambu lalu lintas daripada siswa yang sekolahnya tidak menerima program.